1993
DOI: 10.1073/pnas.90.1.89
|View full text |Cite
|
Sign up to set email alerts
|

A hepatitis B virus pre-S-retinoic acid receptor beta chimera transforms erythrocytic progenitor cells in vitro.

Abstract: In this report, we investigated the transforming properties of retinoic acid receptor 13 (RARfi). The v-erbA protein, which is the viral oncogenic homologue of the thyroid hormone receptor, was replaced by either the complete RAROB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The ®nding that the liver represents a possible target for oncogenic versions of the retinoic acid receptors is not unprecedented. We had previously reported hepatic pathologies in chicken infected by retroviruses transducing an hepatitis B virus-retinoic acid receptor b (HBV-RARb) hybrid protein (Dejean et al, 1986;Garcia et al, 1993). It is interesting to note that the same HBV-RARb chimera was able to transform hematopoietic progenitor cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The ®nding that the liver represents a possible target for oncogenic versions of the retinoic acid receptors is not unprecedented. We had previously reported hepatic pathologies in chicken infected by retroviruses transducing an hepatitis B virus-retinoic acid receptor b (HBV-RARb) hybrid protein (Dejean et al, 1986;Garcia et al, 1993). It is interesting to note that the same HBV-RARb chimera was able to transform hematopoietic progenitor cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Woodchuck Hepatitis Virus, the Hepadnavirus infecting woodchucks, induces liver cancer by recurrent targeting of myc oncogenes (c-myc, N-myc and N-myc2) (Buendia, 1992), and rare cases of HBV integration into key cellular genes have been reported in human liver tumors (retinoic acid receptor beta (Dejean et al, 1986) and Cyclin A (Wang et al, 1990)) and cell lines (mevalonate kinase (Graef et al, 1994)). Moreover, earlier studies have demonstrated that HBV-DNArelated RAR and Cyclin A insertional mutagenesis has transforming activity in vitro and in vivo (Garcia et al, 1993;Berasain et al, 1998). However, recurrent HBV integration sites targeting cellular genes have never been identified in the past (Matsubara and Tokino, 1990), suggesting that insertional mutagenesis does not play a significant role in liver carcinogenesis.…”
mentioning
confidence: 99%
“…HBV-DNA integration may directly promote genetic instability or lead to cisactivation of growth-related genes (Paterlini and Bre chot, 1994). In certain isolated cases, the viral genome was found to be integrated into the Retinoic acid receptor b gene (Dejean et al, 1986), and Cyclin A2 gene (Wang et al, 1990), leading to the expression of chimeric transcripts and proteins, the transforming activity of which was subsequently proved (Berasain et al, 1998;Garcia et al, 1993). Reports have also been made of HBV-DNA integration in the gene encoding mevalonate kinase in the PLC/PRF/5 cell line (Graef et al, 1994), and in the Carboxypeptidase N locus in a human HCC (Pineau et al, 1996).…”
Section: Introductionmentioning
confidence: 99%